Previable Preeclampsia Diagnosed by Renal Biopsy in Setting of Novel Diagnosis of C4 Glomerulopathy - Jessica Parrott; Timothy A. Fields; Marc Parrish (Hindawi Limited, 2017)
Background. Preeclampsia diagnosed before 20 weeks' gestational age is a rare entity, particularly without any predisposing factors. We report a case of preeclampsia occurring prior to 20 weeks' gestational age in the setting of a novel diagnosis of C4 glomerulopathy. Case. A G3P0020 at 18 weeks presented with new onset hypertension and proteinuria, requiring multiple antihypertensive agents to maintain control. Renal biopsy demonstrated thrombotic microangiopathic lesions and glomerular endotheliosis. C4-dominant staining and numerous subendothelial and mesangial electron dense deposits were found within the glomerulus. With no other definable etiologies, preeclampsia was diagnosed. She developed posterior reversible encephalopathic syndrome and pregnancy termination was recommended. Conclusion. The lectin complement pathway may play a role in the pathophysiology of severe, early onset preeclampsia. Renal biopsy may play an integral role in diagnosis.